(untitled) (Research, Society and Development, 2020)
Objective: In order to characterize the actions and protocols in the State and Municipality of São Paulo in confronting the new Coronavirus (Sars-Cov-2), we conducted a literature review looking for public actions or policies, protocols and action plans aiming at a better post-pandemic prognosis of Covid-19, we conducted a literature review looking for public actions or policies, protocols and action plans aiming at a better post-pandemic prognosis for Covid-19. Methodology: We chose to survey articles published in Portuguese, between January 2020 and July 2020, on the database platforms BIREME, LILACS, Virtual Health Library (VHL), and Scientific Eletronic Library Online (SciELO) using the following descriptors: “Covid-19”, “public policies” and “protocols”. Discussion: The emergence of containing the spread of the disease led to the implementation of restrictive measures, such as home isolation of suspected cases and quarantine of home contacts, but also social distance in the entire population, as well as the closing of schools and universities as well as the use of masking required. Results: The role of the nurse and the entire medical team was essential and vital for coping with the pandemic after guidelines from WHO and MS in Brazil. The study presented is relevant in that it summarizes the main actions and protocols published on the State and Municipality of São Paulo in the fight against this pandemic unprecedented in the 21st century.